Sustained Correction of OTC Deficiency in Spf (ash) mice Using Optimized Self-complementary AAV2/8 Vectors - Wang, Lili (2011)
Ornithine transcarbamylase deficiency (OTCD) is the most common inborn error of urea synthesis. Complete OTCD can result in hyperammonemic coma in the neonatal period which can rapidly become fatal. Current acute therapy involves dialysis; chronic therapy involves the stimulation of alternate nitrogen clearance pathways; and the only curative approach is liver transplantation. AAV vector based gene therapy would add to current treatment options provided the vector delivers high level and stable transgene expression in liver without dose limiting toxicity. In this study, we employed an AAV2/8-based self-complementary (sc) vector expressing the murine OTC gene under a liver-specific thyroxine-binding globulin (TBG) promoter and examined the therapeutic effects in a mouse model of OTCD, the spf (ash) mouse. Seven days after a single intravenous injection of vector, treated mice showed complete normalization of urinary orotic acid, a measure of OTC activity. We further improved vector efficacy by incorporating a Kozak or Kozak-like sequence into mOTC cDNA which increased the OTC activity by 5- or 2-fold and achieved sustained correction of orotic aciduria for up to 7 months. Our results demonstrate that vector optimizations can significantly improve the efficacy of gene therapy.